Penerapan E-Government di Desa Penglumbaran Bali - Zulmasyhur, Zulmasyhur; Setiawan, Heru Dian; L. W., Nicolaus Petrus (Jurnal Governansi, 2024)
This research focuses on critical urgency considering the limited explanation in the literature regarding improving digital governance at the village level, especially in Penglumbaran Village, Bali, in the context of E-Government. This urgency arises primarily from the need to understand the practices implemented by village governments in realizing good governance that is responsive to the needs of all village residents. Meanwhile, the main objective of this research is to investigate and analyze improvements in digital governance in Penglumbaran Village, Bali, focusing on implementing E-Government and its impact on administrative efficiency, transparency, and community participation. Then, the descriptive analytical-qualitative method used in this research is supported by a desk study approach, where secondary data relevant to the research topic is used as the basis for analysis. In addition, through implementing the Online Digital Village Administration, Penglumbaran Bali Village has succeeded in increasing the accessibility of government services and strengthening village governance. It is illustrated in research findings, which positively impact efficiency, transparency, and community participation in government decision-making. Therefore, this research provides significance for understanding the effectiveness of digital governance in the context of E-Government at the village level. Thus, this research opens up the potential to support improvements in digital governance at the village level more broadly, aligning with modern government developments.